The Man in the Moon - Joyce, William, 1957-; Bass, L. G. (Laura Geringer) (New York : Atheneum Books for Young Readers, 2011)
When a newly orphaned baby in the moon makes friends with the children of Earth, he begins to shine as brightly as possible to ward off their fears.
"The Guardians of Childhood"--Cover.
Pub Weekly, July 2011
2.3
K-3
Keywords: Moon -- Juvenile fiction; Moon -- Fiction; Moon -- Fiction; Picture books for children